Autoantibody-Negative Immune-Mediated Necrotizing Myopathy Responds to Early and Aggressive Treatment: A Case Report - Marotta, Dario A (Cureus, 2020)
Immune-mediated necrotizing myopathy (IMNM) is a rare idiopathic disease that is further classified by the presence of serum antibodies. A modicum of patients lack serum autoantibodies. Significantly elevated creatine kinase (CK) is highly characteristic of IMNM. The pathophysiology of IMNM is partially understood, and effective treatment options are limited, particularly in patients without serum autoantibodies. In this case, we report a 76-year-old male presenting with a four-month history of proximal muscle weakness. Muscle biopsy and serology confirmed the diagnosis of autoantibody-negative IMNM. Early and aggressive treatment with high-dose steroids and a course of intravenous immunoglobulin significantly reduced the patient’s symptoms and CK within three months. This case serves as an example of an effective treatment outcome in a patient with this rare idiopathic necrotizing myopathy.